Kompetensi Guru dalam Membentuk Profil Pelajar Pancasila: Studi Literatur atas Peran Guru sebagai Fasilitator Nilai - Pramudita, Sevia Ashri Tri; Utomo, Muhamad Wahyu; Madyarini, Dyan Desi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesias educational curriculum transformation adopted in Kurikulum Merdeka is focused on shaping a value-based Indonesias characteristic future learners, Profil Pelajar PancaSila. This paper aims to systematically review literature regarding teachers competency in shaping Profil Pelajar Pancasila, in particular, the implementation of teachers as value facilitators. During the literature study on national accredited journals since 2020, it is obvious that teachers role is vital in the internalization of Pancasila values to learners by use of a contextual and student-oriented learning approach. However, many challenges face the proper implementation of the role such as lack of proper training, minimal understanding of the concept, and environmental and technologic influence. Proposed solutions will involve designing P5-based instructional module, continuous training, and the creation of stakeholder partnership. The findings of this study provide both theoretical and practical contributions to support the character development of Indonesian students through active and reflective teacher engagement.